(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the events of the last years of “perestroika” in Zaporiz’ka region. Basing upon the information taken from private archives, the author demonstrates main tendencies of social and political situation development in Zaporizhzhya in critical years of “perestroika” (1989-1991) and characterizes the positions of Zaporizhzhya local organization of the Communist Party of Ukraine towards its main opponent and rival – Rukh (People’s Movement).